Providing management options to control corn mouse (Calomys musculinus) reservoir populations using a cohort structured model - Piacenza, M. F. (2011)
Fil: Piacenza, M. F. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Buenos Aires; Argentina.